1994
DOI: 10.1002/eji.1830240403
|View full text |Cite
|
Sign up to set email alerts
|

T helper type 1 development of naive CD4+ T cells requires the coordinate action of interleukin‐12 and interferon‐γ and is inhibited by transforming growth factor‐β

Abstract: It was observed in vitro and in vivo that both interferon (IFN)-gamma and interleukin (IL)-12 can promote the development of T helper type 1 (TH1) cells. Since IL-12 was shown to be a costimulator for the production of IFN-gamma by T or natural killer (NK) cells, IL-12 might play only an indirect role in TH1 differentiation by providing IFN-gamma which represents the essential differentiation factor. Using anti-CD3 monoclonal antibody (mAb) for activation of naive CD4+ T cells in the absence of accessory cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
143
0
1

Year Published

1998
1998
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 273 publications
(157 citation statements)
references
References 40 publications
10
143
0
1
Order By: Relevance
“…2A): the ratio of IL-4 ϩ to IFN-␥ ϩ cells was Ͼ3-fold and that of IL-5 ϩ to IFN-␥ ϩ was Ͼ9-fold (Fig. 2B), indicative of a Th2 phenotype and consistent with published results (33,34). In contrast, under identical conditions, ␥␦ T cells from both B6 and BALB/c mice had a reversed IL-4 (IL-5)/IFN-␥ ratio, with predominant production of IFN-␥ and much less IL-4 or IL-5 ( Fig.…”
Section: Il-12 Is Dominant Over Il-4 In ␥␦ T Cell Differentiationsupporting
confidence: 91%
See 1 more Smart Citation
“…2A): the ratio of IL-4 ϩ to IFN-␥ ϩ cells was Ͼ3-fold and that of IL-5 ϩ to IFN-␥ ϩ was Ͼ9-fold (Fig. 2B), indicative of a Th2 phenotype and consistent with published results (33,34). In contrast, under identical conditions, ␥␦ T cells from both B6 and BALB/c mice had a reversed IL-4 (IL-5)/IFN-␥ ratio, with predominant production of IFN-␥ and much less IL-4 or IL-5 ( Fig.…”
Section: Il-12 Is Dominant Over Il-4 In ␥␦ T Cell Differentiationsupporting
confidence: 91%
“…Stimulation of CD4 ϩ ␣␤ T cells by anti-CD3, or by specific peptide for TCR transgenic cells, in the presence of IL-4 and IL-12 leads to a Th2 phenotype; e.g., IL-4 is dominant over IL-12 in ␣␤ T cell differentiation (33,34). To determine the effects of the combination of IL-4 and IL-12 on ␥␦ T cells, CD62L high CD44 low naive ␥␦ T cells, purified by sorting from spleens of B6 TCR ␤ Ϫ/Ϫ mice, and total ␥␦ T cells purified from spleens of TCR-intact BALB/c mice were cultured with coated anti-CD3 and soluble anti-CD28 in the presence of both cytokines.…”
Section: Il-12 Is Dominant Over Il-4 In ␥␦ T Cell Differentiationmentioning
confidence: 99%
“…Previous studies demonstrated that lactoferrin is capable of enhancing BCG-infected macrophage production of IL-12:IL-10 ratio [34], thus generating a cytokine environment that is favorable for promotion of T H 1 immunity [24][25][26]. It was hypothesized that lactoferrin also enhanced efficacy of the BCG vaccine in vivo, in part, by modulating the ability of macrophages to present antigen and for subsequent stimulation of T-cells.…”
Section: Discussionmentioning
confidence: 99%
“…The IL-12 assists in directed development of naïve CD4 + T-cells towards the T H 1 subtype [24][25][26]. In addition, IL-12 functions as a co-stimulator for maximizing production of IFN-γ from T H 1 cells and activates IFN-γ production from memory T-cells [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…Lactoferrin possesses a wide range of immunomodulatory activities [17][18][19] [20] [21] including promotion of the T-cell dominated DTH response towards BCG antigens [22,23], The ability of lactoferrin to enhance the generation of antigen specific DTH responses suggests that lactoferrin could promote development of specific T-cell responses against a complex antigen, such as BCG [24,25] The development of T-cell helper type 1 (T H 1) immunity is, in part, regulated by production of IL-12 [26,27]. A variety of in vivo studies have shown lactoferrin capable of increasing production of IL-12 [28][29][30].…”
Section: Introductionmentioning
confidence: 99%